Sub-fecundity and associated factors among mothers with natural planned conception attending antenatal care service in Arba Minch Health Facilities - Feyisa, Jira Wakoya (PLoS One, 2020)
BACKGROUND: Fecundity is a physiological ability to have children. The inability to get the desired child which was commonly caused by the prolonged time to conceive due to unwanted non-conception period increased from time to time. As a result, many couples are developing psychological, social, and economic problems and unstable life. However, information on fecundity status is limited in Ethiopia context. Therefore, this study aimed to assess the proportion of sub-fecundity and associated factors in Ethiopia context. METHODS: A health institution based cross-sectional study was conducted in Arba Minch health facilities from March 25 to April 25, 2020. By using a systematic sampling method, 539 mothers were selected for the study. Structured questionnaire was used for data collection. A binary logistic regression model was used to identify factors associated with the sub-fecundity. Variables with p-value <0.25 in the bi-variable logistic regression analysis were interred and checked for association in a multivariable logistic regression model. The level of statistical significance was declared at p-value <0.05. RESULT: The proportion of sub-fecundity was 17.8% with 95%CI (14.8%-21.3%). Mothers’ age ≥ 30 (AOR = 2.54, 95%CI; 1.18–5.48), partners’ age ≥ 35 (AOR = 2.20, 95%CI; 1.01–4.75), coffee consumption of ≥ 4 cups/day (AOR = 2.93, 95%CI; 1.14–7.53), menses irregularity (AOR = 3.79 95%CI; 2.01–7.14) and coital frequency of 1day/week (AOR = 3.65, 95%CI; 1.47–9.05) were significantly associated with the sub-fecundity. CONCLUSION: This study found that a substantial proportion of mothers were sub-fecund. Factors that contributed to the sub-fecundity were pre-pregnancy; mothers’ age, partners’ age, coffee drinking of ≥ 4 cups/day, coital frequency of 1day/week, and menses irregularity. Thus, efforts to prevent sub-fecundity should focus on awareness creation as to plan to conceive at early age, reducing coffee consumption, increasing days of coital frequency per week, and investigating and treating mothers with irregular menses.